Prognostic stratification of patients with low-risk hypertrophyc cardiomyopathy: the role of myocardial deformation imaging and myocardial fibrosis. (4th February 2022) - Lo Voi, A; Falletta, C; Madaudo, C; Bellavia, D; Di Lisi, D; Di Gesaro, G; Gentile, G; Mina", C; Novo, S; Nugara, C; Romano, G; Clemenza, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Hypertrophic cardiomyopathy (HCM) is associated with a high incidence of adverse cardiovascular events. Risk stratification for major cardiac events and management of HCM patients are still a serious challenge in cardiology. Current ESC guidelines recommend stratifying the risk of sudden cardiac death (SCD) at 5 years using a prediction model which evaluates clinical and echocardiographic criteria but this model does not include parameters of myocardial deformation at echocardiography and myocardial fibrosis at cardiac magnetic resonance. Purpose: The aim of this study was to evaluate the predictive prognostic role of myocardial deformation imaging parameters derived by echocardiography (left ventricular global longitudinal strain GLS and PALS) and magnetic resonance parameters (extension of delayed enhancement DE) in a population of patients with HCM with low-risk of SCD, considering ESC prediction model. Methods: We enrolled 166 patients, mean age 56.25 ± 16 with hypertrophic cardiomyopathy. A complete echocardiogram and a cardiac magnetic resonance were performed. After a period of 2.5 years, adverse cardiovascular events were evaluated: number of ICD shocks and ventricular arrhythmias, occurrence of atrial fibrillation (AF) or other supraventricular arrhythmias, symptoms of heart failure (HF) and or hospitalizations, heart transplant and death. Results: 7 heart transplants, 8 deaths, 29 patients developed AF, 6 patients developed ventricular arrhythmias and/or ICD shock, 17 patients were hospitalized, 16 patients developed HF. Patients with cardiovascular events had significantly lower PALS values than patients without events (PALS 4.6 ± 2.6 vs 17.5 ± 3.26, p-value < 0.0001) and higher values left atrial volume (179 ± 81 vs 76 ± 37, p-value < 0.001); significantly greater DE extension (57 ± 20 vs 17 ± 19, p-value 0.0082), lower GLS and EF values (GLS 10 ± 3 vs 15 ± 4, p value 0.0033; EF p-value 0, 0001). Patients who developed ventricular arrhythmias, did not show significant changes in EF (p-value 0.26), left atrial volume (90 ± 17, p-value 0.36) and PALS (18 ± 1, p-value 0.7), but they had significantly lower GLS values (5.7 ± 12, p-value 0.02) and a greater extent of DE (p-value 0.04). Patients with AF showed a significantly increased left atrial volume (100 ± 43, p 0.0034) and the PALS (10.8+ 5.9, p-value < 0.0001) was significantly reduced compared to patients without events; EF, GLS (-11.8 ± 8, p-value 0.08) and DE were not significantly reduced (14.8 ± 8, p-value 0.14). In patients who developed HF, both EF, GLS (p-value 0.035), left atrial volume, PALS (p-value < 0.0001) and DE (65 ± 22.5 p-value < 0.0001) were altered compared to patients without events. Conclusion: Low PALS, reduced EF and GLS and higher DE extension and left atrial volume, appear to be prognostic factors in patients with HCM. PALS and left atrial volume are predictors of death, heart failure and AF. Low GLS and DE are predictors of ventricular arrhythmias and heart failure.